2012
DOI: 10.1159/000339151
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pressure-Induced Mechanical Stretch on Vascular Wall Differential Gene Expression

Abstract: High blood pressure is responsible for the modulation of blood vessel morphology and function. Arterial hypertension is considered to play a significant role in atherosclerotic ischaemic heart disease, stroke and hypertensive nephropathy, whereas high venous pressure causes varicose vein formation and chronic venous insufficiency and contributes to vein bypass graft failure. Hypertension exerts differing injurious forces on the vessel wall, namely shear stress and circumferential stretch. Morphological and mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
152
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(164 citation statements)
references
References 242 publications
2
152
0
7
Order By: Relevance
“…This is also in agreement with the data previously published by Fede et al who detected the same tendency for the internalization of AuNPs (w/o PEG) in HUVEC under static and flow conditions using a microfluidic system. 36 In addition to shear stress, cyclic stretch is also a prominent hemodynamic force which acts on endothelial cell function and membrane traffic 17,37 and may alter the internalization of nanoparticles in endothelial cells. As previously reported, we showed that stretch affects the interaction of endothelial cells with amorphous silica nanoparticles and leads to a reduced internalization.…”
Section: Resultsmentioning
confidence: 99%
“…This is also in agreement with the data previously published by Fede et al who detected the same tendency for the internalization of AuNPs (w/o PEG) in HUVEC under static and flow conditions using a microfluidic system. 36 In addition to shear stress, cyclic stretch is also a prominent hemodynamic force which acts on endothelial cell function and membrane traffic 17,37 and may alter the internalization of nanoparticles in endothelial cells. As previously reported, we showed that stretch affects the interaction of endothelial cells with amorphous silica nanoparticles and leads to a reduced internalization.…”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanisms controlling the response of SMCs to mechanical stress have not been fully clarified, it seems that mechanical stretch is transmitted to the SMCs through macromolecular protein complexes, such as transmembrane integrins binding with intracellular adaptors (e.g., paxillin and vinculin) and signaling proteins (focal adhesion kinases) [36][37][38]. Macroscopically, stent placement induces straightening of arterial segments, slightly altering the distribution of shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…One theory is that an elevated pulse pressure causes greater stretching of the arteries, which induces fatigue and fracture of the elastic elements and thus is likely to hasten the development of intimal damage that leads to atherosclerosis. Another theory is that elevated blood pressure promotes inflammatory activation of the arterial wall, which increases the risk of atherosclerosis (Chae et al, 2001;Amer et al, 2011;Anwar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…They are widely distributed in the organs and sera of various animals, including humans. Studies have demonstrated a role for sulfatides in atherogenesis and vascular inflammation resulting in atherosclerosis (Hara et al, 1996;Anwar et al, 2012). An increase in sulfatide was found in both lipoprotein and atherosclerotic plaques in the Watanabe heritable hyperlipidemic rabbit -an animal model for human familial hypercholesterolemia -and was intimately correlated with the development of atherosclerosis (Hara et al, 1996).…”
Section: Discussionmentioning
confidence: 99%